A model for the analysis of timing jitter in OFDM systems - Tomba, L.; Krzymien, W.A. (1998 IEEE International Conference on Communications, 1998)
Multicarrier systems are gaining much attention for their possible application to the design of wideband wireless networks for both indoor and outdoor environments. We present a method for the evaluation of the bit error rate (BER) degradation in orthogonal frequency division multiplexing (OFDM) systems when the sampling instant is affected by timing jitter. We model the timing jitter by a stationary random process with a known statistic and we describe the error caused by it as additive noise. This decomposition is useful because it allows for the analytical determination of the BER. The method may be applied for both uncoded and coded input data sequences.